Implicature of Paper Town Script by John Green’s Movie - Wahid, Muhammad; Afkar, Rijalul (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Implicature is the study of how to understand the speaker’s meaning which is stated indirectly. This study deals with conversational implicature found Paper Towns movie script in John Green’s movie. The objectives of the study are to analyse the types of implicature used in the debate and to explains the ways of performing implicature used by the characters. The qualitative research was used in this research. Grice’s conversational implicature (1975) was applied in analysing the data. The result showed that there were two types of conversational implicature used by the characters, namely: generalized conversational implicature and particularized conversational implicature. There were 4 generalized conversational implicature and 16 particularized conversational implicature. It was found four violations of maxims namely maxim of quantity, maxim of quality, maxim of manner, and maxim of relevance. Margo mostly violated relevance maxim. Through the implicatures the characters tried to convince the hearers, hide some information, keep a secret, express feeling and reject invitation.